Pore-scale heat transfer analysis in grain piles via X-ray CT and LBM - Xiaoliang Wang; Ying Zhou; Yaping Shi; Yanbo Hui; Ju Gao; Yihui Wang; Fan Yang (Journal of Food Engineering, 2026)

Deep learning-enabled real-time acoustofluidic sorting for selective microalgae recovery under wastewater-relevant heterogeneous conditions - Zihan Li; Xian Jiang; Wenzhe Gong; Aoyang Tang; Yan Ma; Xia Du; Yaping Xie; Tielin Shi; Zhiyong Liu; Guanglan Liao; Lei Nie (Bioresource Technology, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

A subset of cell cycle regulators co-expresses with cholesterol pathway and innate immune signaling during early GCRV infection in CIK cells - Waqar Younas; Lei Zhang; Mijuan Shi; Hong Yang; Yingyin Cheng; Wanting Zhang; Yaping Wang; Xiao-Qin Xia (Fish & Shellfish Immunology, 2026)

A Survey of the Species Origins of Common Fish Cell Lines—With a Particular Focus on the Grass Carp Ovarian Cell Line ( GCO ) - Hong Yang; Mijuan Shi; Yingyin Cheng; Wanting Zhang; Bin Gui; Rong Huang; Yaping Wang; Xiao‐Qin Xia (Journal of Fish Diseases, 2026)
Cell line misidentification or contamination undermines the reliability of research outcomes. In this study, we verified the species origin of commonly used fish cell lines, with a particular focus on the grass carp ovarian cell line (GCO). RNA‐seq data from 146 samples of 11 widely used fish cell lines were collected from public databases (NCBI‐SRA) and were mapped to the reference genomes of eight species. GCO RNA‐seq samples from three Chinese laboratories showed a mapping rate of 21.64% ± 3.61% to the grass carp genome, but 89.81% ± 4.83% to the fathead minnow genome. Further transcriptomic similarity analysis revealed that these GCO RNA‐seq samples clustered more closely with cell lines originating from fathead minnow. Targeted analysis of the COI gene amplification region confirmed that nearly all reads from GCO RNA‐seq samples mapped exclusively to the fathead minnow COI amplicon. Collectively, these results indicate that GCO may have undergone cross‐contamination or species misidentification. This study raises doubts about the true species origin of the GCO cell line and proposes that COI DNA barcoding can be used to discriminate the species origin of fish cell lines.

Elevated oxygen partial pressure reduces population exposure to hypoxia over the Qinghai–Xizang Plateau - Yanqiang Chen; Ying Zhang; Yaping Wang; Qinmei Han; Gangfeng Zhang; Xiaoyue Liu; Peijun Shi; Cunrui Huang (Science Bulletin, 2026)

Fracture evolution and differential mechanical response of surrounding rock in deep tunnel excavation: A case study under complex geological conditions - Xiaojun Yu; Xizhi Zhang; Xia-Ting Feng; Feiyan Wang; Ming Shi; Chengxiang Yang; Huanzhen Luo; Yaping Yang; Yushan Wang (Engineering Geology, 2026)

Influences of microplastic-dissolved organic matter-arsenic interactions on arsenic fate in geogenic contaminated groundwater: Mechanistic insights from kinetic-thermodynamic investigations and modeling - Yaping Zhang; Kunfu Pi; Xianjun Xie; Ziyi Xiao; Jianbo Shi; Qianyong Liang; Yuxia Li (Applied Geochemistry, 2026)

A novel retrieval of global dust optical depth and effective diameter based on MODIS thermal infrared observations - Jianyu Zheng; Hongbin Yu; Yaping Zhou; Yingxi Shi; Zhibo Zhang; Claudia Di Biagio; Paola Formenti; Alexander Smirnov (Remote Sensing of Environment, 2026)

Beyond static imaging: A dynamic decision paradigm for robust array-SAR in diverse sensing scenarios - Xiangdong Ma; Xu Zhan; Xiaoling Zhang; Yaping Wang; Jun Shi; Shunjun Wei; Tianjiao Zeng (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Accessibility analysis and optimization strategies of green spaces for enhancing climate resilience: Equity-oriented insights from megacities - Yaping Zhang; Jianjun Zhang; Xuelian Shi; Yixin Dai (Environmental Science & Policy, 2025)

The dual-function of VN catalytic sites at cathode and anode toward high-performance lithium‑sulfur batteries - Yaping Yan; Yi Yang; Liu Yang; Xuefeng Luo; Guangzhao Wang; Qingquan Xue; Andreu Cabot; Hua Kun Liu; Shi Xue Dou; Zixu Sun (Chemical Engineering Journal, 2025)

Permeability prediction of bulk wheat for storage based on micro-computed tomography and lattice Boltzmann method - Xiaoliang Wang; Ying Zhou; Yaping Shi; Qiao Wang; Yanbo Hui; Haiyang Ding (Biosystems Engineering, 2025)

Ghβ-LCY1 influences metabolism and photosynthetic in Gossypium hirsutum - Yanmin Qian; Yaping Wang; Yu Zhang; Zongyan Chu; Mengxin Shen; Cheng Zhang; Lihua Huang; Zhihua Yang; Kaiwen Ren; Yuanyuan Shi; Tingting Jiao; Baoting Yang; et al. (Plant Science, 2025)

Landscape indices explain different responses of runoff and sediment yield to land use/cover change on the Loess Plateau, China - Yanli Qin; Peng Shi; Yuan Hu; Qiang Li; Yaping Wang; Qiaoqiao Wang; Duoduo Zhou (CATENA, 2025)

Gonadal expression profiles reveal the underlying mechanisms of temperature effects on sex determination in the large-scale loach (Paramisgurnus dabryanus) - Lei Zhang; Yutong Fang; Mijuan Shi; Keyi Ren; Xin Guan; Waqar Younas; Yingyin Cheng; Wanting Zhang; Yaping Wang; Xiao-Qin Xia (Animal Reproduction Science, 2025)

Seasonal relative humidity recorded in tree-ring earlywood and latewood δ18O in the West Tianmu Mountains, southeastern China - Hui Wang; Yaping Zhang; Congcong Xiao; Shiyuan Shi; Jiarui Xu; Michael E. Meadows; Jiangfeng Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Influence of dissolved and non-aqueous phase toluene on spectral induced polarization signatures of soils - Yalin Song; Xiaoqing Shi; André Revil; Yaping Deng (Journal of Hazardous Materials, 2024)

Association Between Neuroinflammation and Parkinson’s Disease: A Comprehensive Mendelian Randomization Study - YiNi Wang; XinYu Shi; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Bai-Xiang Li; Kun Ma (Molecular Neurobiology, 2024)

SNCA is a potential therapeutic target for COVID-19 infection in diffuse large B-cell lymphoma patients - Can Chen; Yun Li; Yiwei Li; Zhenzhen Chen; Pengfei Shi; Yaping Xie; Shenxian Qian (Apoptosis, 2024)
Cuprotosis related genes (CRGs) have been proved to be potential therapeutic targets for coronavirus disease 2019 (COVID-19) and cancer, but their immune and molecular mechanisms in COVID-19 infection in Diffuse Large B-cell Lymphoma (DLBC/DLBCL) patients are rarely reported. Our research goal is first to screen the key CRGs in COVID-19 through univariate analysis, machine learning and clinical samples. Secondly, we determined the expression and prognostic role of key CRGs in DLBCL through pan-cancer analysis. We validated the expression levels and prognosis using multiple datasets and independent clinical samples and validated the functional role of key CRGs in DLBCL through cell experiments. Finally, we validated the expression levels of CRGs in COVID-19 infected DLBCL patients samples and analyzed their common pathways in COVID-19 and DLBCL. The results show that synuclein-alpha (SNCA) is the common key differential gene of COVID-19 and DLBCL. DLBCL cells confirm that high expression of SNCA can significantly promote cell apoptosis and significantly inhibit the cycle progression of DLBCL. High expression of SNCA can regulate the binding of major histocompatibility complexes (MHCs) and T cell receptor (TCR) by regulating immune infiltration of Dendritic cells, effectively enhancing T cell-mediated anti-tumor immunity and clearing cancer cells. In conclusion, SNCA may be a potential therapeutic target for COVID-19 infection in DLBCL patients. Our study provides a theoretical basis for improving the clinical treatment of COVID-19 infection in DLBCL patients.

A thermo-hydro-mechanical simulation on the impact of fracture network connectivity on the production performance of a multi-fracture enhanced geothermal system - Zhihong Lei; Yulong Zhang; Xingjie Lin; Yu Shi; Yunhui Zhang; Ling Zhou; Yaping Shen (Geothermics, 2024)

Analysis of the Relationship Between Parkinson’s Disease and Diabetic Retinopathy Based on Bioinformatics Methods - XinYu Shi; YiNi Wang; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Kun Ma; Bai-Xiang Li (Molecular Neurobiology, 2024)

Effects of nanoplastic exposure during pregnancy and lactation on neurodevelopment of rat offspring - Lei Tian; Yaping Zhang; Jiang Chen; Xuan Liu; Huipeng Nie; Kang Li; Huanliang Liu; Wenqing Lai; Yue Shi; Zhuge Xi; Bencheng Lin (Journal of Hazardous Materials, 2024)

Molecular Cloning and Characterization of Scavenger Receptor Class B Type 1 in Grass Carp (Ctenopharyngodon idellus) and Its Expression Profile following Grass Carp Reovirus Challenge - Yang Zhang; Jiayuan Shi; Yuntao Lu; Qing Luo; Pengfei Chu; Rong Huang; Kunci Chen; Jian Zhao; Yaping Wang; Mi Ou (Fishes, 2024)
As a member of the pattern recognition receptor (PRR) class, scavenger receptor class B type 1 (SRB1) plays a key role in innate immunity. Grass carp (Ctenopharyngodon idellus) ranks among the most extensively cultivated freshwater aquaculture species in China. However, little is known about the function of SRB1 in C. idellus. In this research study, a SRB1 gene was identified in C. idellus, named CiSRB1. The full-length cDNA of CiSRB1 is 2486 bp long, with an open reading frame (ORF) of 2486 bp encoding a 497 amino acid (aa) protein containing a conserved CD36 domain. The identified genomic DNA length of CiSRB1 is 20,042 bp, including 12 exons and 11 introns. The predictive analysis of protein interactions revealed that CiSRB1 could interact with the outer capsid proteins of typical GCRV strains. The tissue distribution of CiSRB1 exhibited age-dependent characteristics. CiSRB1 displayed the highest expression in the intestines and moderate levels in muscle, spleen, liver, and brain of one-year-old grass carp while maintaining relatively low levels in three-year-old grass carp. Following grass carp reovirus (GCRV) infection, notable upregulation of CiSRB1 transcripts was observed in major immune tissues (gills, intestines, spleen, and liver). Furthermore, significant differences were found between one-year-old and three-year-old grass carp, with lower CiSRB1 expression levels being detected in the older group. Additionally, a distinct response to GCRV infection was observed in one-year-old and three-year-old grass carp. It was found that one-year-old individuals had a mortality rate of up to 84% 6 days post-infection (dpi), whereas all three-year-old counterparts survived after GCRV infection. The analysis of GCRV copy numbers across tissues revealed substantially higher levels in one-year-old grass carp compared with their older counterparts, confirming the existence of age-dependent susceptibility to GCRV infection in grass carp. Combined with these results, it was speculated that the decline in cell-surface CiSRB1 expression with age may impede reovirus binding to host cells, potentially explaining why older grass carp demonstrated enhanced resistance to GCRV infection. This observation accentuates the importance of CiSRB1 in the context of GCRV infection and provides insights into age-dependent susceptibility to reovirus.

Sediment resuspension and transport in the offshore subaqueous Yangtze Delta during winter storms - Min Tian; Haifei Yang; Wenxiang Zhang; Kehui Xu; Benwei Shi; Yaping Wang; Shilun Yang (Frontiers in Marine Science, 2024)
Storm-induced episodic sediment redistribution in coastal systems can reshape geomorphic bodies, disrupt ecosystems, and cause economic damage. However, cold-wave-storm-induced hydrodynamic changes and residual sediment transport in large, exposed subaqueous deltas, such as the Yangtze Delta, are poorly understood because it is typically expensive and difficult to obtain systematic field data in open coast settings during storm events. We conducted a successful field survey of waves, currents, changes in water depth, and turbidity at a station (time-averaged water depth of 20 m) in the offshore subaqueous Yangtze Delta over 10 days during winter, covering two storms and two fair-weather periods. During the storm events, strong northerly winds drove southward longshore currents (~0.2 m/s) and resulted in increased wave height and sediment resuspension, thereby leading to massive southward sediment transport. In contrast, both southward and northward transports were limited during the fair-weather periods. A better understanding of the storm-induced sediment transport can be obtained by using an approximately half-day lag in sediment transport behind wind force, given the time needed to form waves and longshore drift, the inertia of water motion, and the slow settling velocity of fine-grained sediment. Our results directly support previous findings of southward sediment transport from the Yangtze Delta during winter, which is deposited in the Zhejiang–Fujian mud belt in the inner shelf of the East China Sea. In addition, the southward sediment transport from the Yangtze Delta occurs mainly during episodic storm events, rather than during the winter monsoon, and winter storms dominate over typhoons in driving southward sediment transport from the delta. This study highlights the importance of storms, especially during winter storms, in coastal sediment redistribution, which is of particular significance when considering the projected increase in storm intensity with global warming.

Flexible and wearable functional materials for ionizing radiation Protection: A perspective review - Hao Li; Linping Yan; Jibo Zhou; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2024)

Unraveling the stereoscopic gene transcriptional landscape of zebrafish using FishSED, a fish spatial expression database with multispecies scalability - Cheng Guo; Weidong Ye; Danying Cao; Mijuan Shi; Wanting Zhang; Yingyin Cheng; Yaping Wang; Xiao-Qin Xia (Science China Life Sciences, 2024)

PSAT1 promotes autophagy to resist insufficient autophagy caused by cigarette smoke extract in human airway epithelial cells - Lixing Wang; Furong Yan; Yongbin Shi; Xiaoshan Su; Yaping Zhang (Toxicology in Vitro, 2024)

Calcium signal regulated carbohydrate metabolism in wheat seedlings under salinity stress - Ya Zhang; Dan Qiao; Zhe Zhang; Yaping Li; Shuqian Shi; Yingli Yang (Physiology and Molecular Biology of Plants, 2024)

Unprecedented early summer warming recorded in tree rings on the central eastern Tibetan Plateau over the past three centuries - Jiangfeng Shi; Hui Wang; Jinbao Li; Shiyuan Shi; Jiarui Xu; Yaping Zhang; Huayu Lu (Climate Dynamics, 2023)

Research progress on pharmacological effects and mechanisms of cepharanthine and its derivatives - Liangliang Shi; Shuaizhe Wang; Shangzu Zhang; Jiawei Wang; Yaping Chen; Yangyang Li; Zhiwei Liu; Sichen Zhao; Benjun Wei; Liying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Optimal operation strategy of peak regulation combined thermal power units and concentrating solar power plant with energy conversion and spinning reserve - Yunyun Yun; Dahai Zhang; Lixin Li; Yaping Li; Yiru Shi; Jinghan He (Journal of Cleaner Production, 2023)

Characterization of DNAPL source zones in clay-sand media via joint inversion of DC resistivity, induced polarization and borehole data - Xueyuan Kang; Christopher Power; Amalia Kokkinaki; André Revil; Jichun Wu; Xiaoqing Shi; Yaping Deng (Journal of Contaminant Hydrology, 2023)

Scalable production of polyamide-6/graphene composites with enhanced electromagnetic shielding and thermal conductivity - Rahul Navik; Huijun Tan; Hao Zhang; Zhiyuan Liu; Qixuan Xiang; Liyun Shi; Shiming Lu; Yaping Zhao (Chemical Engineering Journal, 2023)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)

Distribution of benthic macrofaunal communities in intertidal flat under hydrodynamic influence: a case study of Jiangsu coast, East China - Longhui Zhang; Dezhi Chen; Shu Gao; Yaping Wang; Benwei Shi; Yongfen Du (Journal of Oceanology and Limnology, 2023)

Disruption of phosphate metabolism and sterol transport-related genes conferring yeast resistance to vanillin and rapid ethanol production - Fengguang Zhao; Yaping Zhang; Jian Hu; Ce Shi; Xiang Ao; Shengding Wang; Ying Lin; Zhongwei Sun; Shuangyan Han (Bioresource Technology, 2023)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Gene expression in the microbial consortia of colonial Microcystis aeruginosa ‐a potential buoyant particulate biofilm - Limei Shi; Yuanfeng Cai; Shengling Gao; Daoyan Fang; Yaping Lu; Pengfu Li; Qinglong L. Wu (Environmental Microbiology, 2022)
Microcystis spp., notorious bloom‐forming cyanobacteria, are often present in colony form in eutrophic lakes worldwide. Uncovering the mechanisms underlying Microcystis colony formation and maintenance is vital to controlling the blooms, but it has long been a challenge. Here, bacterial communities and gene expression patterns of colonial and unicellular forms of one non‐axenic strain of Microcystis aeruginosa isolated from Lake Taihu were compared. Evidently, different microbial communities between them were observed through 16S rDNA MiSeq sequencing. Metatranscriptome analyses revealed that transcripts for pathways involved in bacterial biofilm formation, such as biosynthesis of peptidoglycan and arginine by Bacteroidetes , methionine biosynthesis, alginate metabolism, flagellum, and motility, as well as widespread colonization islands by Proteobacteria , were highly enriched in the colonial form. Furthermore, transcripts for nitrogen fixation and denitrification pathways by Proteobacteria that usually occur in biofilms were significantly enriched in the colonial Microcystis . Results revealed that microbes associated with Microcystis colonies play important roles through regulation of biofilm‐related genes in colony formation and maintenance. Moreover, Microcystis colony represents a potential ‘buoyant particulate biofilm’, which is a good model for biofilm studies. The biofilm features of colonial Microcystis throw a new light on management and control of the ubiquitous blooms in eutrophic waters.

Biparental genetic mapping reveals that CmCLAVATA3 (CmCLV3) is responsible for the variation in carpel number in melon (Cucumis melo L.) - Lihuan Wang; Yaping Wang; Feishi Luan; Xian Zhang; Jingchao Zhao; Zhongzhou Yang; Shi Liu (Theoretical and Applied Genetics, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Enhancement of oral bioavailability and anti-hyperuricemic activity of aloe emodin via novel Soluplus®—glycyrrhizic acid mixed micelle system - Feng Shi; Lin Chen; Yaping Wang; Jing Liu; Michael Adu-Frimpong; Hao Ji; Elmurat Toreniyazov; Qilong Wang; Jiangnan Yu; Ximing Xu (Drug Delivery and Translational Research, 2022)

Pandemic threat posed by H3N2 avian influenza virus - Yaping Zhang; Conghui Zhao; Yujie Hou; Yan Chen; Fei Meng; Yichao Zhuang; Liling Liu; Yasuo Suzuki; Jianzhong Shi; Guohua Deng; Hualan Chen (Science China Life Sciences, 2021)

Pituitary Adenylate Cyclase-Activating Polypeptide Protects Against Cognitive Impairment Caused by Chronic Cerebral Hypoperfusion - Xiaosu Guo; Ye Tian; Yaping Yang; Shiping Li; Li Guo; Jiong Shi (Molecular Neurobiology, 2021)

Structural elucidation of fucoidans from Sargassum pallidum - Xin Liu; Bin Liu; Xiaolei Wei; Yaping Shi; Airong Jia; Changyun Wang (Journal of Applied Phycology, 2021)

Gene UCHL1 expresses specifically in mouse uterine decidual cells in response to estrogen - Lishuang Hao; Di Song; Mengfei Zhuang; Yan Shi; Lin Yu; Yaping He; Jian Wang; Tingting Zhang; Zhaogui Sun (Histochemistry and Cell Biology, 2020)

Characterization of longshore currents in southern East China Sea during summer and autumn - Peng Li; Benwei Shi; Yangang Li; Sijian Wang; Xin Lv; Yaping Wang; Qing Tian (Acta Oceanologica Sinica, 2020)

Laboratory experiments demonstrate that the hissing of the Chinese alligator can effectively inhibit movement of flower fish Ptychobarbus kaznakovi - Guoyong Liu; Yujiao Wu; Xiujun Shen; Yaping Hu; XiHuo Qin; Weixin Tian; Liming Liu; Xiaoling Wang; Xiaotao Shi (Hydrobiologia, 2019)

Immunity induced by recombinant attenuated IHNV (infectious hematopoietic necrosis virus)‐G N438A expresses VP2 gene‐encoded IPNV (infectious pancreatic necrosis virus) against both pathogens in rainbow trout - Yaping Chen; Mengting Guo; Yanxue Wang; Xiaojing Hua; Shuai Gao; Yuting Wang; Dechuan Li; Wen Shi; Lijie Tang; Yijing Li; Min Liu (Journal of Fish Diseases, 2019)
Infectious hematopoietic necrosis virus (IHNV) and infectious pancreatic necrosis virus (IPNV) are important pathogens in rainbow trout farming worldwide. Their co‐infection is also common, which causes great economic loss in juvenile salmon species. Development of a universal virus vaccine providing broadly cross‐protective immunity will be of great importance. In this study, we generated two recombinant (r) virus (rIHNV‐N438A‐ΔNV‐EGFP and rIHNV‐N438A‐ΔNV‐VP2) replacing the NV gene of the backbone of rIHNV at the single point mutation at residue 438 with an efficient green fluorescent protein ( EGFP ) reporter gene and antigenic VP2 gene of IPNV. Meanwhile, we tested their efficacy against the wild‐type (wt) IHNV HLJ‐09 virus and IPNV serotype Sp virus challenge. The relative per cent survival rates of two recombinant viruses against (wt) IHNV HLJ‐09 virus challenge were 84.6% and 81.5%, respectively. Simultaneously, the relative per cent survival rate of rIHNV‐N438A‐ΔNV‐VP2 against IPNV serotype Sp virus challenge was 88.9%. It showed the two recombinant viruses had high protection rates and induced a high level of antibodies against IHNV or IPNV. Taken together, these results suggest the VP2 gene of IPNV can act as candidate gene for vaccine and attenuated multivalent live vaccines and molecular marker vaccines have potential application for viral vaccine.

Spatial and temporal precipitation patterns characterized by TRMM TMPA over the Qinghai-Tibetan plateau and surroundings - Ziqiang Ma; Yaping Xu; Jie Peng; Qiuxiao Chen; Dan Wan; Kang He; Zhou Shi; Hongyi Li (International Journal of Remote Sensing, 2018)

Stocks and dynamics of particulate and dissolved organic matter in a large, shallow eutrophic lake (Taihu, China) with dense cyanobacterial blooms - Limei Shi; Yaxin Huang; Yaping Lu; Feizhou Chen; Min Zhang; Yang Yu; Fanxiang Kong (Journal of Oceanology and Limnology, 2018)

Genetic Diversity of Benthic Microbial Eukaryotes in Response to Spatial Heterogeneity of Sediment Geochemistry in a Mangrove Ecosystem - Ping Zhu; Yaping Wang; Tiantian Shi; Guoqiang Huang; Jun Gong (Estuaries and Coasts, 2018)

Delineation of contaminant plume for an inorganic contaminated site using electrical resistivity tomography: comparison with direct-push technique - Qing Liao; Yaping Deng; Xiaoqing Shi; Yuanyuan Sun; Weidong Duan; Jichun Wu (Environmental Monitoring and Assessment, 2018)

Accumulation and tolerance characteristics of lead in Althaea rosea Cav. and Malva crispa L. - Yaping Huang; Lihong Zu; Meili Zhou; Cong Shi; Guangshuang Shen; Fuchen Shi (Biologia, 2018)

Three new oleanane-type triterpenoid saponins from the seeds of Celosia cristata L. - Xin Liu; Jifa Zhang; Kai Guo; Airong Jia; Miansong Zhang; Yaping Shi; Changheng Liu; Linlin Xiao; Zhenliang Sun (Natural Product Research, 2018)

Assessing the vulnerability of changing coasts, Hainan Island, China - Yaping Wang; Benwei Shi; Liang Zhang; Jianjun Jia; Xiaomin Xia; Liang Zhou; Rui Yu; Yang Yang; Jianhua Gao (Acta Oceanologica Sinica, 2017)

The response of sedimentary record to catchment changes induced by human activities in the western intertidal flat of Yalu River Estuary, China - Yong Shi; Zhishuai Liu; Jianhua Gao; Yang Yang; Yaping Wang (Acta Oceanologica Sinica, 2017)

Analysis of the characteristics of offshore currents in the Changjiang (Yangtze River) estuarine waters based on buoy observations - Peng Li; Benwei Shi; Yaping Wang; Weihua Qin; Yangang Li; Jian Chen (Acta Oceanologica Sinica, 2017)

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD - Yaping Yan; Yujing Li; Ying Fu; Li Yang; Lei Su; Kaibin Shi; Minshu Li; Qiang Liu; Aimee Borazanci; Yaou Liu; Yong He; Jeffrey L. Bennett; et al. (Science China Life Sciences, 2016)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

Single nucleotide polymorphisms in PDCD6 gene are associated with the development of cervical squamous cell carcinoma - Bin Zhou; Peng Bai; Hui Xue; Zhu Zhang; Shaoqing Shi; Kui Zhang; Yanyun Wang; Kana Wang; Yi Quan; Yaping Song; Lin Zhang (Familial Cancer, 2015)

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

Effect of chlorogenic acid on LPS-induced proinflammatory signaling in hepatic stellate cells - Haitao Shi; Lei Dong; Xiaoyan Dang; Yaping Liu; Jiong Jiang; Yan Wang; Xiaolan Lu; Xiaoyan Guo (Inflammation Research, 2013)

Modulation of hsa-miR-26b levels following adipokine stimulation - Guangfeng Xu; Chenbo Ji; Chunmei Shi; Hailong Fu; Lingling Zhu; Lu Zhu; Lulian Xu; Ling Chen; Yueying Feng; Yaping Zhao; Xirong Guo (Molecular Biology Reports, 2013)

Multiple origins of Tibetan Y chromosomes - Yaping Qian; Binzhi Qian; Bing Su; Jiankun Yu; Yuehai Ke; Zhengtao Chu; Lei Shi; Daru Lu; Jiayou Chu; Li Jin (Human Genetics, 2000)